Stock Index Ranking and Performance Evaluation of Shanghai Stock Exchange (SSE) Using AHP and TOPSIS Method - Singhai, Sanjay Kumar; Awasthi, Vineet Kumar (International Journal of Computer Sciences and Engineering, 2025)
Stock Index selection process is tough in financial domain and complicated in decision making process, especially when selected criterion is confecting in nature. Multi criteria decision-making (MCDM) methods like Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) are most commonly used method for decision making process in financial domain. This paper utilizes AHP and TOPSIS method for ranking of indices. Three financial year data of five stock indices from Shanghai Stock Exchange (SSE) with four criteria are considered in stock index ranking process. Experimental result reveals that SSE IT TELECOMMUNICATION index is preformed consistently well for all three financial years in case of both AHP and TOPSIS method